Evidence for the embodiment of the automatic approach bias - Solzbacher, Johannes; Czeszumski, Artur; Walter, Sven; König, Peter (Frontiers in Psychology, 2022)
Tendencies of approach and avoidance seem to be a universal characteristic of humans. Specifically, individuals are faster in avoiding than in approaching negative stimuli and they are faster in approaching than in avoiding positive stimuli. The existence of this automatic approach/avoidance bias has been demonstrated in many studies. Furthermore, this bias is thought to play a key role in psychological disorders like drug addiction and phobias. However, its mechanisms are far from clear. Theories of embodied cognition postulate, that the nature of gestures play a key role in this process. To shed light on the role of the involved gesture we employed a 2x2 factorial design with two types of stimuli. Participants had either to approach positive and avoid negative stimuli (congruent conditions) or to avoid positive stimuli and approach negative stimuli (incongruent conditions). Further, they responded either with a joystick or a button press on a response pad. Participants reacted faster in congruent conditions, i.e., avoiding negative stimuli and approaching positive stimuli, then in incongruent conditions. This replicates the known approach and avoidance bias. However, directly analyzing the button press condition participants revealed no reaction time advantage for congruent trials compared to incongruent trials. In contrast, in the joystick condition participants were significantly faster performing congruent reactions than incongruent reactions. This interaction, a significant reaction time advantage, when the response is enacted by moving a joystick towards or away from the body gives evidence that approach-avoidance tendencies have a crucial bodily component.